Nimbus-7 TOMS Antarctic ozone atlas: August - December 1990 - Krueger, Arlin J.; Larko, David E.; Penn, Lanning M.; Scott, Courtney J.; Doiron, Scott D.; Guimaraes, Patricia T. (1991)
Because of the great environmental significance of ozone and to support continuing research at the Antarctic and other Southern Hemisphere stations, the development of the 1990 ozone hole was monitored using data from the Nimbus-7 Total Ozone Mapping Spectrometer (TOMS) instrument, produced in near-real-time. This Atlas provides a complete set of daily polar orthographic projections of the TOMS total ozone measurements over the Southern Hemisphere for the period 1 Aug. through 31 Dec. 1990. The 1990 ozone hole developed in a manner similar to that of 1987 and 1989, reaching a comparable depth in early October. This was in sharp contrast to the much weaker hold of 1988. The 1990 ozone hole remained at polar latitudes as it filled in Nov., in contrast to other recent years when the hold drifted to mid-latitudes before disappearing. Daily ozone values above selected Southern Hemisphere stations are presented, along with comparisons of the 1990 ozone distribution to that of other years. A new calibration scheme (Version 6) was used to process 1990 ozone values, as well as to reprocess those of previous years.